2022
DOI: 10.3389/fpsyt.2022.966758
|View full text |Cite
|
Sign up to set email alerts
|

Association between depressive symptoms and diagnosis of diabetes and its complications: A network analysis in electronic health records

Abstract: ObjectivesDiabetes and its complications are commonly associated with depressive symptoms, and few studies have investigated the diagnosis effect of depressive symptoms in patients with diabetes. The present study used a network-based approach to explore the association between depressive symptoms, which are annotated from electronic health record (EHR) notes by a deep learning model, and the diagnosis of type 2 diabetes mellitus (T2DM) and its complications.MethodsIn this study, we used anonymous admission no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…Those with diabetes at Wave 4 were predominately (87.74%) people with relatively new (within the last 5-7 years) diagnoses of diabetes. This is in line with recent research by Wan et al (2022), which found a statistically significant increase in depressive symptom connectivity in the 2 years following diagnosis. In contrast, Airaksinen et al (2020) found the connectivity of depressive symptoms remained unchanged before and after diagnosis (Airaksinen et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Those with diabetes at Wave 4 were predominately (87.74%) people with relatively new (within the last 5-7 years) diagnoses of diabetes. This is in line with recent research by Wan et al (2022), which found a statistically significant increase in depressive symptom connectivity in the 2 years following diagnosis. In contrast, Airaksinen et al (2020) found the connectivity of depressive symptoms remained unchanged before and after diagnosis (Airaksinen et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…They found that although the mean level of depressive symptoms increased after diagnoses, these changes were not reflected in the depressive network structure. Recent research, also examining depressive symptoms in individuals before and after diagnosis of type 2 diabetes or hypertension, found a significant increase in depressive symptom connectivity (Wan et al, 2022). However, in both studies depressive symptoms were scored using binary values (1 for yes, and 0 for no), and therefore the network models may suffer from a lack of specificity of the strength of depressive symptom interactions.…”
Section: Introductionmentioning
confidence: 99%